Knowledge sharing in organization: A systematic review - Asiamah Yeboah (Cogent Business & Management, 2023)
The main objective of this paper is to bring together scattered literature on knowledge sharing, and analyse them to provide a better understanding of the concept and to suggest emerging directions for future research. The review went through three stages: setting the review protocol, administering the review, and reporting the review. The paper systematically reviewed 110 articles under three research streams: (1) knowledge sharing enablers (2) knowledge sharing processes, and (3) knowledge sharing outcomes. The paper found that little is known about the kind of knowledge that better contributes to develop the competencies required for specific market, there is over-concentration on knowledge sharing enablers than barriers, knowledge sharing process is not linked to the overall firm objective and strategy, and financial outcomes of knowledge sharing has been studied more than nonfinancial outcomes. Based on these findings, organisations have been advised to design knowledge sharing processes in line with their overall business objective, strategy, and resources at their disposal to maximise the benefits of knowledge sharing.
Keywords: 650; enablers; innovation capability; Knowledge sharing; organizational performance; outcomes; processes